Analisis Kinerja Berdasarkan Tingkat Efisiensi Perbankan Syariah - Arifah, Aulia Nur; Mohammad Yunies Edward (Fakultas Ekonomi dan Bisnis Islam, 2023)
The purpose of this study is to identify performance based on the efficiency level of Sharia Commercial Banks in Indonesia in 2020 period using the DEA method and the CRS model with an intermediation approach. This study also compares efficiency results using five indicators without looking at the actual target and three indicators looking at the actual target. Furthermore, this study uses 10 Sharia Commercial Banks as a sample. Overall, the results of research on the efficiency level of Sharia Commercial Banks in Indonesia conducted during a certain research period have not consistently reached an optimal level of efficiency, where most of the efficiency levels are still below 100 percent. Policy recommendations for Sharia Commercial Banks to increase the level of efficiency are to control and allocate optimal resources and then increase their output capacity by maintaining existing inputs.